IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDEO PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS III SDN 12 PALANGKA RAYA - Thomas, Orbit; Simpun; Riski (Jurnal Teknologi Pendidikan, 2025)
This study aimed to describe student learning and teaching activities as well as the improvement of learning outcomes through the implementation of the Problem-Based Learning (PBL) model assisted by instructional videos in the subject of Pancasila Education. The background of this study was conventional and monotonous classroom practices which lowered students’ motivation and performance. This study employed a Classroom Action Research (CAR) method using Kurt Lewin’s model in two cycles. The subjects were five third-grade students of SDN 12 Palangka. The results showed an increase in students’ average scores from 67 (pre-test) to 79.5 (cycle I) and 92.5 (cycle II). Classical completeness also increased from 40% to 100%. Both teacher and student activities improved to the “very good” category. Thus, the implementation of the PBL model assisted by video effectively enhanced students’ learning outcomes in Pancasila Education.